Clinical Review of Abdominal Acupuncture Method on Treating Insomnia - Chang, Shu Jiun (2015)
Objective: To study the effect of abdominal acupuncture method on treating insomnia with past clinical cases and academic writing. Methods: Collection of the literature reviews of the abdominal acupuncture is compiled. Analysis of the modification of the abdominal acupuncture method is recorded while trials by others Chinese physicians’ experience are assessed and compared. Clinical trials are done as supplementing evidence with efficiency rate determined through patient’s symptoms improvement, Pittsburgh Sleeping Quality Index (PSQI). Discussion: Sun’s abdominal acupuncture method therapy can treat insomnia through improve the Stomach and Spleen’s condition and regulate the emotional of the patients. The improvement of the patients collected is marked improved, 59.70%. Conclusion: Sun’s Abdominal Acupuncture method therapy of treating insomnia is effective.